PATRIOTISM AND ITS CONTEXTUALIZATION IN THE MILLENNIAL ERA: STUDY OF TAFSIR MARĀH LABĪD BY SYEKH NAWĀWĪ AL-BANTENĪ - Hamid, Ali; Alsounusi, Salih Abdulrahman (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2023)
This paper discusses patriotism in the context of the millennial era through an analysis of the interpretation of Marāh Labīd by Syekh Nawāwī Al-Bantenī. This research explores Al-Bantenī’s views on the values of patriotism and how these views are relevant in the millennial era implied in his commentary. The textual analysis method is used to identify Al-Bantenī’s views on love for the motherland, obligations to the state, and participation in community development. The results of this study provide insight that according to Al-Bantenī, patriotism in the Qur’an is at least implied in QS. Al-Taubah [9]: 71, QS. Al-Baqarah [2]: 126, QS. Al-Nisā’: [4]:59, and QS. Al-Maidah [5]:2. Sheikh Nawāwī Al-Bantenī's interpretation of the five characteristics of patriotism above is still relevant in the millennial era. Considering that the millennial generation is the generation of hope for the nation. They are expected to become leaders and provide better change for the nation in the future. In addition, by looking at the characters possessed by the millennial generation, the character is good at socializing to establish friendships which creates an attitude of responsibility and a confident character to express defenses. One of its applications is to establish communities that care about others and invite the millennial generation to participate in several discussion forums